Association of fertility diet score with endometriosis: a case–control study - Ghasemisedaghat, Sakine; Eslamian, Ghazaleh; Kazemi, Seyyedeh Neda; Rashidkhani, Bahram; Taheripanah, Robabeh (Frontiers in Nutrition, 2023)
Abstract Background and aims: Different factors, such as environmental, epigenetic, genetic and immunological, have been identified as potential risks for developing endometriosis. However, the correlation between dietary patterns and endometriosis is currently unknown. The aim of this study was to explore the potential link between fertility diet score and the odds of endometriosis. Methods: This study was a hospital-based case–control study that took place in a gynecology clinic in Tehran, Iran, between February 2021 and January 2022. A total of 107 newly diagnosed endometriosis cases and 210 controls were included. The participants' habitual diets were evaluated using a food frequency questionnaire, and their fertility diet score was estimated using a point system based on Chavarro et al.'s criteria. The logistic regression was utilized to calculate the odds ratios (OR) with 95% confidence intervals (CIs). Results: The study found that women who adherence to fertility diet have a lower odds of endometriosis. This was observed in both the base model and the adjusted model, with a significant decrease in odds of endometriosis by 66% (OR = 0.44, 95%CI = 0.27-0.71, P = 0.001) and 54% (aOR = 0.46, 95%CI = 0.23-0.90, P =0.022), respectively. Additionally, consuming vegetable proteins and multivitamins were also associated with lower odds of endometriosis. On the other hand, consuming animal proteins, heme iron, and having a high glycemic load were associated with significantly higher odds of endometriosis. Conclusions: Our research supports the hypothesis that following a fertility diet may decrease the odds of endometriosis in Iranian women. However, these findings should be verified through extensive, prospective studies.